The COVID-19 pandemic and journalistic ethics: Spanish citizens’ demand for external control of health communication in the media - Maciá-Barber, Carlos (Frontiers in Communication, 2024)
The disinformation that threatened media coverage in Spain during the COVID-19 pandemic was perceived as a serious threat by the population, which became a crucial ethical challenge for health information. This nationwide study is part of a global research project whose primary objective was to know and delve further into the behavior of citizens in the face of journalistic information related to COVID-19, to determine the channels used by audiences to learn about the pandemic and their personal informative interaction through social networks (Twitter, Facebook, Instagram). The field sample (June 2022) comprised 1,800 online surveys (carried out using the CAWI system) of persons aged 18 years and older residing in the country. Quotas were established by sex, age and Autonomous Community. The sampling error is ±2.34, with a confidence level of 95.5% and p = q = 0.5. The data collected were processed with the IBM SPSS Statistics 26 package. The results confirm a majority belief (values 4 + 5/5) that journalism pursues the truth (59.5%). They also show in adults the predominance of a high confidence in their ability to detect falsehoods, as opposed to the low self-perception confessed by young people. Inversely proportional is the verifying effort of these population groups. There is no homogeneous agreement that discrimination against vulnerable groups (obese people, smokers, the elderly, migrants) was encouraged despite the medium-high caliber of the assessment (3.35/5.00). The most notorious finding was to confirm the majority social demand (values 4 + 5/5 = 72.6%) to implement some external control on the professional collective that guarantees ethical adequacy and quality in the informative coverage of health issues, which suggests a system of journalistic co-regulation.